Perception of the use of teaching videos in preclinical training of Chilean dentistry students, 2013. - Jessica Goset; Pedro Espinoza (Universidad de Concepción., 2014)
The use of educational videos is a valuable tool in preclinical dental training, as long as the pedagogical objectives match the appropriate learning stage. Accordingly, this teaching innovation suggests the realization of three types of didactic videos inserted in a specially designed pedagogical methodology for the preclinical cycle. After half a semester of use, quantitative results yielded a positive perception in relation to the promotion of evaluation criteria and conflictual tone development. On the other hand, perception of negotiation promotion and reaching consensus was divided into positive and negative. Both the analysis of frequency access to online videos and category formation clearly highlight the importance students give to demonstrative videos as well as the teacher's role when using them. By way of conclusion, it can be said that students considered educational videos, especially the demonstrative type, as a useful tool for developing conflictual tone and evaluation criteria, being always complementary to the role that the teacher who guides their preclinical training plays.